Defect interactions in the non-reciprocal Cahn–Hilliard model - Navdeep Rana; Ramin Golestanian (New Journal of Physics)
We present a computational study of the pairwise interactions between defects in the recently introduced non-reciprocal Cahn–Hilliard model. The evolution of a defect pair exhibits dependence upon their corresponding topological charges, initial separation, and the non-reciprocity coupling constant α . We find that the stability of isolated topologically neutral targets significantly affects the pairwise defect interactions. At large separations, defect interactions are small and a defect pair is stable. When positioned in relatively close proximity, a pair of oppositely charged spirals or targets merge to form a single target. At low α , like-charged spirals form rotating bound pairs, which are however torn apart by spontaneously formed targets at high α . Similar preference for charged or neutral solutions is also seen for a spiral target pair where the spiral dominates at low α , but concedes to the target at large α . Our work sheds light on the complex phenomenology of non-reciprocal active matter systems when their collective dynamics involves topological defects.